Local Density Correlations in Liquids - Egami, Takeshi (Frontiers in Physics, 2020)
The structure and dynamics of liquids and glasses are usually discussed in terms of the short-range atomic structure and the nature of atomic bonds. However, many properties of liquids are rather similar and only weakly dependent on chemistry. Here we suggest that these properties are controlled not so much by the short-range atomic correlations but mainly by the medium-range density correlations which are similar among various liquids and supersede chemical details of the system. Taking metallic alloy liquids as examples we discuss the origin of the medium-range density correlations and argue they are only weakly dependent on the detailed nature of the atomic bond. By extrapolating the coherence of density correlation to infinity we can define an ideal glass state which is very diverse in the local atomic structure but is characterized by long-range density correlations.